Developmental trends in CO2 methanation using various catalysts. Issue 17 (23rd July 2019) - Sreedhar, I.; Varun, Yaddanapudi; Singh, Satyapaul A.; Venugopal, A.; Reddy, Benjaram M.
Abstract : Co2 methanation-two edged sword to counter global warming and energy crisis. Abstract : Global warming has been a serious concern worldwide. Greenhouse gases like CO2 majorly contribute to the rise in average global temperature. Attempts have been made to reduce the CO2 in the atmosphere. However, carbon capture alone was not found to be commercially viable. Various other green and cost-effective methods to convert CO2 into more useful products have been researched. CO2 methanation was found to be one such vital reaction of converting CO2 to useful fuel, like methane, using different catalysts. In this paper, this vital reaction has been reviewed comprehensively. Studies conducted with respect to materials that have proven catalysts such as Ni, synthesised by impregnation, to be the most suitable, where use of promotors (like Si and Ce) and supports (like zeolites, ceria and MOFs), high pressures, low humidity and optimum temperatures have led to increased selectivity, have been presented. The different reactors/contactors that have been used in this process at various scales, their design parameters, process conditions, performance, and limitations have been discussed which have shown the use of annular fixed bed reactors to be the most favourable. The different mechanisms proposed for the reaction, involving various intermediates, mainly carbenes and formates, and problems incurred in low temperature operation and finding of an appropriate support and promotor have been presented. Thermo-kinetic modelling studies on this reaction have also been presented and discussed. Every section has been summarized in the form of a table. The recent advances as well as future challenges and prospects of the above-said aspects of CO2 methanation have also been cited. Recent advances suggest methods of electrocatalytic reduction potentially employing Cu based compounds and perovskite oxides as catalysts, bio-electrocatalytic reduction using microbes as catalysts, and photocatalytic reduction using noble or critical metals including Ni and TiO2 as catalysts and graphene as a support, for the conversion of carbon dioxide to methane.